Integrasi Nilai-Nilai Multikulturalisme dalam Pembelajaran PKn di Sekolah Dasar - Bakar, Abu (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This study aims to analyze how multicultural values are integrated into Civic Education (PKn) learning in elementary schools and their impact on fostering students' tolerance and diversity awareness. This research is a library research using a qualitative approach. The subjects are multiculturalism concepts and theories in education, while the object is the implementation of these values in elementary-level PKn learning. Data collection was conducted through a literature review of relevant academic sources from the last five years, and data were analyzed using descriptive content analysis. The results show that integrating multicultural values into PKn learning helps shape students' character to appreciate cultural differences, act inclusively, and understand the importance of diversity in national life. The conclusion emphasizes the essential role of teachers, school environments, and supportive curricula in promoting multicultural education from an early age.